Isolation and characterization of Campylobacter massiliensis sp. nov., a novel Campylobacter species detected in a gingivitis subject. Issue 10 (20th October 2021) - Antezack, Angéline; Boxberger, Manon; Rolland, Clara; Ben Khedher, Mariem; Monnet-Corti, Virginie; La Scola, Bernard
Abstract : A Gram-negative bacterium, designated strain Marseille-Q3452 T, was isolated from subgingival dental plaque of a subject suffering from dental plaque bioﬁlm-induced gingivitis on an intact periodontium in Marseille, France. The strain was characterized by 16S rRNA and atpA gene sequence analysis and by conventional phenotypic and chemotaxonomic testing. The average nucleotide identity (ANI) and core genome phylogeny were determined using whole-genome sequences. Although strain Marseille-Q3452 T showed 99.72 % 16S rRNA gene sequence similarity with Campylobacter showae strain ATCC 51146 T, atpA and ANI analyses revealed divergence between the two strains. The two species could also be distinguished phenotypically on the basis of the absence of flagella and nitrate reduction. On the basis of the results from phenotypic, chemotaxonomic, genomic and phylogenetic analyses and data, we concluded that strain Marseille-Q3452 T represents a novel species of the genus Campylobacter, for which the name Campylobacter massiliensis sp. nov. is proposed (=CSUR Q3452=CECT 30263).